The shame game : overturning the toxic poverty narrative - O'Hara, Mary (Social affairs journalist) (Policy Press, 2020)
Drawing on a two-year story-telling project and her own experience of childhood poverty, this book by award-winning journalist and author Mary O'Hara, argues for a radical overhaul of the dominant narrative of poverty in the UK and US, using the real experts to try to find answers - the people who live it.